2015
DOI: 10.1097/md.0000000000001091
|View full text |Cite
|
Sign up to set email alerts
|

Delimiting Allelic Imbalance of TYMS by Allele-Specific Analysis

Abstract: Allelic imbalance of thymidylate synthase (TYMS) is attributed to polymorphisms in the 5′- and 3′-untranslated region (UTR). These polymorphisms have been related to the risk of suffering different cancers, for example leukemia, breast or gastric cancer, and response to different drugs, among which are methotrexate glutamates, stavudine, and specifically 5-fluorouracil (5-FU), as TYMS is its direct target. A vast literature has been published in relation to 5-FU, even suggesting the sole use of these polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, TYMS 2R/2R genotype was assessed to be a risk factor for hematological toxicity, and the heterozygous 2R3R TYMS genotype was found in CRC patients with stage III-IV tumors. Previous studies have observed that chemotherapy influences drug response, toxicities and clinical outcomes in patients (Wang et al, 2012;Rosmarin et al, 2015;Zhao et al, 2015;Balboa et al, 2015;Wang et al, 2016). Capecitabine (Xeloda, Roche, oral drug) and 5-FU (pro-drug) are chemotherapeutic drugs commonly given to patients with colorectal cancer (CRC).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, TYMS 2R/2R genotype was assessed to be a risk factor for hematological toxicity, and the heterozygous 2R3R TYMS genotype was found in CRC patients with stage III-IV tumors. Previous studies have observed that chemotherapy influences drug response, toxicities and clinical outcomes in patients (Wang et al, 2012;Rosmarin et al, 2015;Zhao et al, 2015;Balboa et al, 2015;Wang et al, 2016). Capecitabine (Xeloda, Roche, oral drug) and 5-FU (pro-drug) are chemotherapeutic drugs commonly given to patients with colorectal cancer (CRC).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these mechanisms, several factors may influence the development of toxicities or the clinical outcome of CRC, including other gene polymorphisms and alternative cytotoxic paths that are capable of increasing activity and inducing changes in cell physiology to result in neoplastic progression (Gutiérrez et al, 2016). Different studies have observed an association of TYMS 2R/3R with different clinical outcome manifestations (Wang et al, 2012;Rosmarin et al, 2015;Zhao et al, 2015;Balboa et al, 2015;Wang et al, 2016). In this study, we also observed an association of gastric and hematological toxicities in the non-chemotherapy responses of patients carrying 2R/2R-2R/3R genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although knockdown or amplification experiments succeeded in demonstrating the in vitro importance of TYMS in 5-FU resistance and toxicity, clinical studies on the predictive role of these polymorphisms have been controversial so far [ 68 ]. For example, no significant association between TYMS genotype and response rate or overall survival (OS) has been observed in patients with gastric cancer treated with platinum/5-FU combinations.…”
Section: Fluoropyrimidinesmentioning
confidence: 99%